Amblyopia with Co-existing Near Point Disorders: A Case Report. - Optom, Chinmoy Sheet M. (Optometry & Visual Performance, 2016)
Background: Patients with anisometropic amblyopia may often have associated accommodative and vergence dysfunction. In many cases, these associated near point disorders are undiagnosed and untreated. This case shows the different possibilities of associated near point disorders and their management. Case Report: A 15-year-old female patient presented with a complaint of diminished vision in the left eye. She was found to have anisometropic amblyopia. Before starting vision therapy, a comprehensive binocular vision assessment was performed to determine the presence of any co-existing near point vision disorders. Convergence insufficiency, reduced near stereo acuity, accommodative infacility in the amblyopic eye, and accommodative excess in the non-amblyopic eye were documented. This patient was treated with 20 visits of office-based vision therapy with home reinforcement. A post-vision therapy assessment showed marked improvement of visual acuity in the amblyopic eye and stereo acuity and successful treatment of the convergence insufficiency and accommodative dysfunction. Conclusions: Amblyopia can be associated with many other near point vision disorders. A comprehensive binocular vision assessment is recommended before initiating amblyopia therapy.